Overcoming energy constraints on future development in Stellenbosch through energy efficiency : retrofitting of solar hot water heaters and gas stoves in middle and high income households in the residential sector - Nyabadza, Munyaradzi Christine (Stellenbosch : Stellenbosch University, 2012)
Thesis (MPhil)--Stellenbosch University, 2012.